Three ways social identity shapes climate change adaptation. (24th November 2021) - Barnett, Jon; Graham, Sonia; Quinn, Tara; Adger, W Neil; Butler, Catherine
Abstract: Adaptation to climate change is inescapably influenced by processes of social identity—how people perceive themselves, others, and their place in the world around them. Yet there is sparse evidence into the specific ways in which identity processes shape adaptation planning and responses. This paper proposes three key ways to understand the relationship between identity formation and adaptation processes: (a) how social identities change in response to perceived climate change risks and threats; (b) how identity change may be an objective of adaptation; and (c) how identity issues can constrain or enable adaptive action. It examines these three areas of focus through a synthesis of evidence on community responses to flooding and subsequent policy responses in Somerset county, UK and the Gippsland East region in Australia, based on indepth longitudinal data collected among those experiencing and enacting adaptation. The results show that adaptation policies are more likely to be effective when they give individuals confidence in the continuity of their in-groups, enhance the self-esteem of these groups, and develop their sense of self-efficacy. These processes of identity formation and evolution are therefore central to individual and collective responses to climate risks.